OBTAINING MONOMETHYLOLUREAGALLATE ETHERS (Scientific journal of the Fergana State University, 2023)
The studies studied the formation of mono-, di- and trimethylol ureas as a result of the interaction of urea and formaldehyde. The purpose of this study was to study the formation of esters of gallic acid with mono-, di- and trimethylurea. The study used methods of fine organic synthesis, IR, mass spectrometry, melting point measurement, thin layer, column chromatography. The structure of esters showed that the esterification reaction proceeds due to the carboxyl group of gallic acid and the hydroxyl group of methylol ureas.